Nilai Kepentingan Budaya Keanekaragaman Tumbuhan Obat Masyarakat Desa Teluk Rendah Ilir Kabupaten Tebo: Index Cultural Significance of Medicinal Plants in the Community of Teluk Rendah Village, Tebo Ilir District, Tebo Regency - Albayudi, Albayudi; Adriadi, Ade; Budilaksono, Tri; Aini, Yasri Syarifatul; Nur'aini, Hanifah; Mandala, Bakti (Fakultas Kehutanan Universitas Jambi, 2024)
ABSTRACT Indonesia is a country with a high biodiversity, including medicinal plants. Fertile soil, a supportive climate, and flora diversity are significant potential for producing natural-based medicines. The use of plants in traditional medicine has long been practiced by various ethnic groups or communities across Indonesia. One way to document the use and interaction of communities with plants is through ethnobotanical studies. Quantitative ethnobotanical studies analyze plant species that hold significance for communities, aiming to support the valuation of useful plant diversity from both social and economic perspectives. This study focuses on identifying important plant species, particularly medicinal plants, that play a vital role in the lives of the people in Teluk Rendah Village, Tebo Ilir Subdistrict, Tebo Regency. The use of medicinal plants has been a long-standing tradition among the residents of Teluk Rendah Ilir Village, Tebo Ilir Subdistrict, Tebo Regency. The study was conducted from September to October 2020 in Teluk Rendah Ilir Village, Tebo Ilir Subdistrict, Tebo Regency. This research is descriptive-quantitative, employing survey methods, in-depth interviews, and quantitative analysis using the Index of Cultural Significance (ICS). A total of 65 species from 35 families were identified as medicinal plants utilized by the community. The ICS results indicated two medicinal plants with the highest scores: Zingiber officinale with an ICS value of 60 and Citrus aurantifolia with an ICS value of 54. Plants with moderate ICS values included 7 species, while 39 species were categorized as low, and 17 species were categorized as very low. Keywords: ethnobotany, ICS (Index of Cultural Significance), medicinal plants ABSTRAK Indonesia merupakan negara yang kaya akan sumberdaya hayati, termasuk tumbuhan obat. Kesuburan tanah, iklim yang mendukung, serta keanekaragaman flora yang melimpah menjadikan Indonesia sebagai salah satu negara yang memiliki potensi sebagai penghasil obat-obatan dari bahan alam. Penggunaan tumbuhan dalam pengobatan tradisional telah lama dilakukan oleh berbagai suku atau etnis di Indonesia. Salah satu cara pendokumentasian penggunaan dan interaksi masyarakat dengan tumbuhan adalah dengan studi etnobotani. Studi etnobotani kuantitatif dengan menganalisis jenis-jenis tumbuhan yang penting bagi masyarakat dilakukan untuk mendukung upaya valuasi keanekaragaman tumbuhan berguna baik dari nilai sosial dan ekonominya. Studi ini bertujuan untuk mengidentifikasi jenis-jenis tumbuhan khususnya tumbuhan obat yang penting dalam kehidupan masyarakat Desa Teluk Rendah Kecamatan Tebo Ilir Kabupaten Tebo. Penelitian ini bertujuan untuk mengetahui Index Nilai Budaya dari tumbuhan obat yang digunakan oleh masyarakat Desa Teluk Rendah Ilir Kabupaten Tebo. Penelitian ini dilaksanakan pada bulan September-Oktober tahun 2020. Jenis penelitian ini bersifat deskriptif kuantitatif dengan metode survey dan wawancara in-depht interview dan analisis kuantitatif menggunakan analisis nilai kepentingan budaya (Index of Cultural Significanse/ICS). Terdapat sebanyak 65 spesies dari 35 famili yang dimanfaatkan sebagai obat oleh masyarakat Desa Teluk Rendah Illir. Nilai Index Cultural Significance (ICS) menunjukkan 2 jenis tumbuhan obat dengan nilai ICS tertinggi, yaitu Zingiber officinale (jahe merah) dengan nilai ICS sebesar 60 dan Citrus aurantifolia (jeruk nipis) dengan nilai ICS sebesar 54. Tumbuhan dengan dengan nilai ICS kategori moderat/sedang sebanyak 7 spesies, kategori rendah sebanyak 39 spesies dan kategori sangat rendah sebanyak 17 spesies. Kata kunci: etnobotani, ICS (Index of Cultural Significance), tumbuhan obat